The middle classes in the popular imagination - Portocarrero, Gonzalo (1985)
In this article the authors aim at putting together the basic opinions and attitudes held by low-income groups regarding the middle classes, placing special emphasis on the underlying social processes. In other words, the authors explore the subjective dimensión of how social classes perceive each other. The method used is based on the utilization of a projective test especially designed for this research project and of a questionnaire answered by 307 sénior high school students, both in Lima and in other provinces. According to the analysis of the results, the authors arrive to an interpetation of the attitudes and beliefs of low-income youth with regard to wealth and its attainment.​